2009
DOI: 10.1104/pp.109.136762
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection ofVerticilliumWilt Resistance Mediated by Tomato Ve1      

Abstract: Vascular wilt diseases caused by soil-borne pathogens are among the most devastating plant diseases worldwide. The Verticillium genus includes vascular wilt pathogens with a wide host range. Although V. longisporum infects various hosts belonging to the Cruciferaceae, V. dahliae and V. albo-atrum cause vascular wilt diseases in over 200 dicotyledonous species, including economically important crops. A locus responsible for resistance against race 1 strains of V. dahliae and V. albo-atrum has been cloned from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
563
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(573 citation statements)
references
References 66 publications
9
563
0
1
Order By: Relevance
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA sequence of GbWRKY1 was cloned into the TRV plasmid using BamHI and KpnI to construct the TRV:GbWRKY1 VIGS vector and was then transformed into Agrobacterium tumefaciens GV3101 via electroporation as described previously (Fradin et al, 2009). The TRV:00 (control) and TRV: GbWRKY1 vectors were agroinfiltrated into the cotyledons of 10-d-old cv YZ1 plants using a needleless syringe as described previously .…”
Section: Plant Materials Vigs Experiments and Disease Assaysmentioning
confidence: 99%
“…affect (in a nonmutually exclusive manner) phosphorylation events within the PRR-BAK1 complex, association and/or dissociation with downstream components, and phosphorylation events with direct substrates. It is becoming increasingly clear that, in addition to their role in BR responses, BAK1 and other SERKs in Arabidopsis and other plant species are master regulators of plant innate immunity (Heese et al, 2007;Shan et al, 2008;Fradin et al, 2009Fradin et al, , 2011Santos et al, 2009;Bar et al, 2010;Krol et al, 2010;Chaparro-Garcia et al, 2011;Mantelin et al, 2011;Roux et al, 2011;Yang et al, 2011) as well as of cell death control Kemmerling et al, 2007;Gao et al, 2009;Wang et al, 2011), pollen development (Albrecht et al, 2005;Colcombet et al, 2005), and organ abscission (Lewis et al, 2010). One must not assume that the model based on analyses between BRI1 and BAK1 is universal, and, in light of our results, it is essential that researchers analyze in detail and quantify the impact of modifying the SERK proteins in transgenic approaches when studying SERKdependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additional SERKs can be recruited by FLS2 with BKK1 as major regulator besides BAK1 (13). BAK1 also positively regulates other PRR-dependent pathways (12,(14)(15)(16). However, innate immune responses triggered by PAMPs such as fungal chitin do not depend on BAK1 (14,17).…”
mentioning
confidence: 99%